The cultural nature of human development - Rogoff, Barbara (2003)
Este texto contiene : Orienting concepts and ways of understanding the cultural nature of human development. Development as transformation of participation in cultural activities. Individuals, generations and dynamic cultural communities. Child rearing in families and communities. Developmental transitions in individuals roles in their communities.
Keywords: Psicología del Desarrollo